An overview of air interface multiple access for IMT-2000 - Ojanpera, T. (IEEE Communications magazine)
The basis for any air interface design is how the common transmission medium is shared between users (i.e., multiple access scheme). The underlying multiple access method for all mobile radio systems is FDMA. The performance of TDMA and CDMA has been subject to vigorous debate, without any definitive conclusions. This article gives an overview of worldwide research and standardization activities related to the multiple access schemes for third-generation mobile communications systems IMT-2000 and UMTS